Christian Ethical Analysis of the L.A. Riots in 1992: The Media and Institutional Racism - Song, Yong Sup (Religions, 2020)
This essay utilizes Reinhold Niebuhr’s theology of the universality of sin to analyze institutional racism, using the 1992 Los Angeles riots as a case study. Contrary to the conventional interpretation of the riots as a conflict between African Americans and Korean Americans, the pervasive institutional racism of the mainstream media of that era spread the riots into multiracial conflicts, which explains Niebuhr’s thinking regarding the universality of sin. Furthermore, the sensationalism of the media that fueled the massive violence deprived African Americans of the moral dynamic for social transformation and victimized Korean Americans as scapegoats. As a result, the institutional processes promoted the status quo that benefited the white privileged class at the expense of the racial minorities. Implications found in this essay may be applicable to current issues, such as anti-Asian racism that has surfaced during the COVID-19 pandemic in the United States.